2019
DOI: 10.3390/jcm8101751
|View full text |Cite
|
Sign up to set email alerts
|

GSKIP-Mediated Anchoring Increases Phosphorylation of Tau by PKA but Not by GSK3beta via cAMP/PKA/GSKIP/GSK3/Tau Axis Signaling in Cerebrospinal Fluid and iPS Cells in Alzheimer Disease

Abstract: Based on the protein kinase A (PKA)/GSK3β interaction protein (GSKIP)/glycogen synthase kinase 3β (GSK3β) axis, we hypothesized that these might play a role in Tau phosphorylation. Here, we report that the phosphorylation of Tau Ser409 in SHSY5Y cells was increased by overexpression of GSKIP WT more than by PKA- and GSK3β-binding defective mutants (V41/L45 and L130, respectively). We conducted in vitro assays of various kinase combinations to show that a combination of GSK3β with PKA but not Ca2+/calmodulin-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…This process appears connected to GSKIP (GSK3β-Interacting Protein), a small cytosolic AKAP [ 275 ] that directly interacts with both GSK3β and PKA, coordinating their actions. The involvement of a cAMP/GSKIP/GSK3β/PKA/Tau axis in Tau phosphorylation was recently studied in SHSY5Y cells and confirmed in cerebrospinal fluid and pluripotent stem cells of AD patients [ 276 ]. The authors demonstrated the existence of a molecular complex consisting of GSKIP, RII-based PKA, GSK3β and Tau (tethered to GSK3β) that enhances the cAMP/PKA signalling, resulting in increased Tau phosphorylation at distinct PKA-dependent phosphorylation sites (Ser214, Ser262, and Ser409) during AD pathogenesis [ 276 ].…”
Section: Alterations Of Camp Compartmentalization In Neurodegeneramentioning
confidence: 99%
See 1 more Smart Citation
“…This process appears connected to GSKIP (GSK3β-Interacting Protein), a small cytosolic AKAP [ 275 ] that directly interacts with both GSK3β and PKA, coordinating their actions. The involvement of a cAMP/GSKIP/GSK3β/PKA/Tau axis in Tau phosphorylation was recently studied in SHSY5Y cells and confirmed in cerebrospinal fluid and pluripotent stem cells of AD patients [ 276 ]. The authors demonstrated the existence of a molecular complex consisting of GSKIP, RII-based PKA, GSK3β and Tau (tethered to GSK3β) that enhances the cAMP/PKA signalling, resulting in increased Tau phosphorylation at distinct PKA-dependent phosphorylation sites (Ser214, Ser262, and Ser409) during AD pathogenesis [ 276 ].…”
Section: Alterations Of Camp Compartmentalization In Neurodegeneramentioning
confidence: 99%
“…The involvement of a cAMP/GSKIP/GSK3β/PKA/Tau axis in Tau phosphorylation was recently studied in SHSY5Y cells and confirmed in cerebrospinal fluid and pluripotent stem cells of AD patients [ 276 ]. The authors demonstrated the existence of a molecular complex consisting of GSKIP, RII-based PKA, GSK3β and Tau (tethered to GSK3β) that enhances the cAMP/PKA signalling, resulting in increased Tau phosphorylation at distinct PKA-dependent phosphorylation sites (Ser214, Ser262, and Ser409) during AD pathogenesis [ 276 ]. Among several Tau phosphorylation sites associated with neurodegeneration [ 277 , 278 ], Ser262 hyperphosphorylation significantly reduces the affinity of Tau for microtubules [ 279 ] and is associated with the initial steps of AD [ 280 ].…”
Section: Alterations Of Camp Compartmentalization In Neurodegeneramentioning
confidence: 99%
“…CLU1 and ARMC4 contain DUF727; however, CLU1 contains other parts of CLU-N, CLU, CLU central, winged helix-like DNA-binding domains, and tetratricopeptide-like helical domains, but ARMC4 only contains 13X Armadillo repeats [43,44]. DUF refers to a "domain of unknown function" [19][20][21][22][23]45]. A short domain in the clustered mitochondria protein is involved in its mitochondrial cytoplasmic distribution [46,47].…”
Section: Analysis Of Uniprot and Gskip Gene Ontology: Identification Of Compositetype Gskipmentioning
confidence: 99%
“…ARMC4 may function as a competitor to APC and β-catenin. In addition, the pangolin protein (TCF/LEF) is involved in the Wnt signaling pathway in pangolins, an intermediate host species for SARS (modified from [19,51]). https://doi.org/10.1371/journal.pone.0262138.g006…”
Section: Physiological Implications and Importance Of Gskip In Wnt Signalingmentioning
confidence: 99%
“…Furthermore, iPSC-derived forebrain neurons from APP and PSEN1 mutated AD patients were evaluated in phenotype studies and revealed a higher Aβ42/40 ratio and Aβ oligomer accumulations [62][63][64][65][66][67][68][69]. Increased Tau and hyper-phosphorylated Tau protein levels, early endosome accumulation, GSK3β overactivation, and increased reactive oxygen species (ROS) production were also observed in amyloid precursor protein (APP)-mutated forebrain neurons [62,63,65,66,70]. AD-associated astrocytes were themselves neurotoxic and capable of damaging healthy neurons by reducing lactate secretion, increasing Aβ release and cytokine production, and inducing abnormal calcium flux [63,71,72].…”
Section: Patient Ipscs To Modeling and Drug Screening For Admentioning
confidence: 99%